2016
DOI: 10.18632/oncotarget.10458
|View full text |Cite
|
Sign up to set email alerts
|

YAP promotes erlotinib resistance in human non-small cell lung cancer cells

Abstract: Yes-associated protein (YAP) is a main mediator of the Hippo pathway, which promotes cancer development. Here we show that YAP promotes resistance to erlotinib in human non-small cell lung cancer (NSCLC) cells. We found that forced YAP overexpression through YAP plasmid transfection promotes erlotinib resistance in HCC827 (exon 19 deletion) cells. In YAP plasmid-transfected HCC827 cells, GTIIC reporter activity and Hippo downstream gene expression of AREG and CTGF increased significantly (P<0.05), as did ERBB3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(129 citation statements)
references
References 29 publications
(32 reference statements)
6
123
0
Order By: Relevance
“…A number of recent studies have demonstrated that the increased level of YAP was revealed to be associated with increased drug resistance in multiple lines of cancer cells (23,24,29). In the present study, YAP silencing sensitized HCC cells to CDDP, suggesting that YAP induces CDDP resistance in HCC cells.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…A number of recent studies have demonstrated that the increased level of YAP was revealed to be associated with increased drug resistance in multiple lines of cancer cells (23,24,29). In the present study, YAP silencing sensitized HCC cells to CDDP, suggesting that YAP induces CDDP resistance in HCC cells.…”
Section: Discussionsupporting
confidence: 63%
“…Accumulating evidence has indicated that YAP is involved in drug resistance in a variety of cancer cells (22)(23)(24). The present study examined whether YAP is involved in drug resistance in HCC cells.…”
Section: Downregulation Of Yap Enhances the Sensitivity Of Hcc Cells mentioning
confidence: 94%
“…It has been reported that EGFR and c-Met are involved in cell migration (20,(35)(36)(37)(38). In the present study, we showed that migration of the OSCC cell lines SAS and Ca9-22 was regulated by both the EGFR and c-Met signalling pathways.…”
Section: Discussionsupporting
confidence: 61%
“…Verteporfin initially was proposed as a YAP1-TEAD complex inhibitor that prevented YAP1-TEAD interaction [24]. Subsequently, more evidence, including our current study, indicated verteporfin can also decrease YAP1 protein level [39]. The mechanism for YAP reduction by verteporfin is through upregulation of 14-3-3σ, which sequesters YAP1 in the cytoplasm and leads to YAP1 degradation [41].…”
Section: Discussionmentioning
confidence: 75%